2022
DOI: 10.7554/elife.75753
|View full text |Cite
|
Sign up to set email alerts
|

Fracture healing is delayed in the absence of gasdermin-interleukin-1 signaling

Abstract: IL-18. Excessive GSDM-mediated pore formation can compromise the integrity of the plasma membrane thereby causing the lytic inflammatory cell death, pyroptosis. We found that GSDMD and GSDME were the only GSDMs that were readily expressed in bone microenvironment. Therefore, we tested the hypothesis that GSDMD and GSDME are implicated in fracture healing owing to their role in the obligatory inflammatory response following injury. We found that bone callus volume and biomechanical properties of injured bones w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…36 Additionally, the essential role of IL-1β in promoting bone healing after fracture has been confirmed. 35 These findings suggest a complex role for IL-1β in maintaining inflammation and promoting tissue regeneration.…”
Section: Discussionmentioning
confidence: 98%
“…36 Additionally, the essential role of IL-1β in promoting bone healing after fracture has been confirmed. 35 These findings suggest a complex role for IL-1β in maintaining inflammation and promoting tissue regeneration.…”
Section: Discussionmentioning
confidence: 98%
“…When we started to search for literature information about pyroptotic cell death and GSDMD, we could not obtain enough information about its possible influence on the skeletal system. However, later, we noted that one research group had started to focus on GSDMD as a contributing factor to bone remodeling and inflammatory bone loss, [ 20 , 23 ] and this was followed by another very important study from a different group that indicated a novel cell‐autonomous function of GSDMD by caspase‐8 cleavage in the osteoclasts. [ 22 ] The authors showed that the cleavage at Asp88 in addition to Asp275 leads to the accumulation of the shorter N‐terminal p20 fragment in the cytosol, resulting in suppression of the enhanced activation of osteoclasts by RANK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, nonadherent cells were removed by vigorous washes with PBS, and adherent BMMs were detached with trypsin-EDTA and cultured in culture media containing a 1:10 dilution of CMG for various experiments. Murine primary neutrophils were isolated by collecting bone marrow cells and subsequently over a discontinuous Percoll (Sigma-Aldrich, MO, USA) gradient as described previously ( Sun et al, 2022 ). Briefly, all bone marrow cells from femurs and tibias were washed by PBS and then resuspended in 2 ml PBS.…”
Section: Methodsmentioning
confidence: 99%